Accretion disks in the cataclysmic variables - Koen, Marthinus Christoffel (Department of Astronomy, 2016)
The general equations describing the time-independent structure of gaseous circumstellar disks in vertical hydrostatic equilibrium are derived. The possibility of turbulent instablilty and the resulting viscosity laws are discussed.